Gerakan Sosial Baru di Indonesia: Repertoar Gerakan Petani - - Suharko (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2006)
New social movement can be perceived both as a new type of social movements and as a new social science paradigm. The article refers new social movement as the new type of social movements. It article describes and analyzes repertoar of peasant movements in Indonesin as part of new social movement. Peasant movements in Indonesia are actually part of anti globalization movement which have quite similar chamcteristics with new social movements.